(untitled) (Global Journal of Human-Social Science, 2015)
The paper examines the multi-dimensionality of rural agriculture and rural development in terms of productivity, income and welfare in terms of health, nutrition, education and other features of satisfactory life of rural people. It is an integral approach to agricultural production. Both processes are very important considering because more of the bulk of the population in sub-Sahara Africa especially Nigeria lives in rural areas and they experience much misery, poverty, morbidity and under-development. The paper also x-rays the requirements for agricultural and rural development such as a national philosophical base, integrated pilot demonstration, cohesive identity, participatory development, gender mainstreaming among others. Finally, the paper discussed the condition necessary for people oriented agricultural and rural development in Nigeria.